A Contingency View of the Effects of Cognitive Diversity on Team Performance: The Moderating Roles of Team Psychological Safety and Relationship Conflict. (April 2013) - Martins, Luis L.; Schilpzand, Marieke C.; Kirkman, Bradley L.; Ivanaj, Silvester; Ivanaj, Vera
We examined the moderating roles of team psychological safety and relationship conflict on the relationship between two forms of team cognitive diversity—expertise and expertness diversity—and team performance. We found that when team psychological safety was lower, rather than higher, expertise diversity was more negatively related to team performance, but conversely, expertness diversity was more positively related to team performance. When team relationship conflict was lower, rather than higher, expertness diversity was more positively related to team performance. Our findings advance a contingency view of the effects of cognitive diversity on team performance and suggest several implications for theory and practice.